Notions of Non-Mainstream Educational Provision: Understanding the Indonesia Equivalency Programs Among Established Alternative Education Throughout the World - Rosmilawati, Ila (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This article presents the overview of literature regarding the notions of non-mainstream education provision. The main purpose is to provide an overview of how the Indonesia Equivalency Program as an alternative education links to similar systems of education provision around the world. The literature shows variations in the terminology of non-mainstream education for out-of-school youth used interchangeably among countries. The notions of non-formal education, alternative education and second change education are often used and relevant in order to established well-defined axes along which to situate thinking about Indonesia Equivalency Programs. Through alternative education that offers democratic educational experience, the Indonesia Equivalency Programs is an alternative education system, based on the belief that people can make their own choice regarding mainstream or alternative schooling. The Equivalency Programs fits with the notion as a second chance education to caters students who failed in their first attempt. The aims of participating can be varying, from seeking remedial support to help in getting employment, or pursuing lifelong learning.